Purely ornamental? Public perceptions of distributed energy storage in the United Kingdom. (February 2019) - Ambrosio-Albalá, Pepa; Upham, Paul; Bale, Catherine S.E.
Highlights: Focus groups in Leeds (UK) with members of the public with and without of photovoltaic (PV) /battery systems. Differing PV experience had little influence on perceptions of hypothetical domestic and community scale battery storage. Previous poor experiences with local government influences attitudes negatively. Attitudes to scale battery storage were positive to community scale battery storage were sceptical when notions of sharing were involved. Abstract: Distributed energy storage technologies (DES) are expected to help in decarbonising the power sector, decentralising power sources and meeting the mismatch between the produced and consumed energy. However, the likelihood of the use and acceptance of these technologies will partly hinge on public perceptions. Here, we present results of three focus groups and dialogue from the city of Leeds (UK) held with members the lay public with and without personal experience of technology (photovoltaic panels) about public perceptions of distributed energy storage technologies at household and community scale. We apply and adapt the Energy Cultures framework, which was initially developed for understanding energy behaviours as mediated by individual psychological factors, by practice-based, energy-related culture and infrastructural elements. Accordingly, we connect what people think, do and have in energy contexts, to better understand perceptions of DES technologies as part of a broader renewable energy landscape (culture) that is both materially and socially constructed. We show how a variety of elements such as forms of energy consumption; costs; expectations of family members; previous experiences; perceptions of government and the municipal authority; and expectations about the technologies, are likely to shape acceptance and adoption of battery storage at the household and community level.